CRIMINAL LIABILITY OF PIMPS IN HUMAN TRAFFICKING: A Case Study of 32/Pid.Sus/2024/PN Tkn - Wahyuni, Rezeki Ananda Putri; Surya, Achmad (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2025)
The aim of this research is to explore the factors influencing the Takengon District Court Judge's decision in case Number 32/Pid.Sus/2024/PN Tkn and to evaluate the criminal accountability associated with prostitution pimping (Case Study Number: 32/Pid.Sus/2024/PN Tkn). This research employs a normative, juridical, and prescriptive methodology, utilizing both the statute and case approaches. The findings indicated that the judge's rationale for the ruling in Number 32/Pid.Sus/2024/PN Tkn highlighted aggravating factors, specifically the defendant's actions disrupting the community and the harm caused to Aceh's reputation as the Mecca Porch, along with mitigating circumstances regarding the defendant. From a legal standpoint, this case should involve three parties subject to penalties in keeping with Article 23, paragraph (1) of Qanun Aceh Number 6 of 2021 related to Jinayat Law, since Aceh has specific Islamic laws that categorically forbid prostitution.